2014
DOI: 10.1016/j.jacc.2014.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors, and Prognostic Impact of Late Bleeding Complications After Transcatheter Aortic Valve Replacement

Abstract: MLBCs after TAVR were frequent and associated with increased mortality. Better individualized and risk-adjusted antithrombotic therapy after TAVR is urgently needed in this high-risk population. (THE PARTNER TRIAL: Placement of AoRTic TraNscathetER Valve Trial; NCT00530894).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
113
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(126 citation statements)
references
References 42 publications
6
113
1
5
Order By: Relevance
“…Recently, Généreux and coworkers draw attention to late bleeding events after hospital discharge 18. With an analysis on the incidence, predictors, and the prognostic impact of late bleeding complications post‐TAVI in the PARTNER patient population, these investigators observed a strong and independent association of late bleeding and mortality after 12 months of follow‐up (HR adj , 3.91; 95% CI, 2.67 to 5.71; P <0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Généreux and coworkers draw attention to late bleeding events after hospital discharge 18. With an analysis on the incidence, predictors, and the prognostic impact of late bleeding complications post‐TAVI in the PARTNER patient population, these investigators observed a strong and independent association of late bleeding and mortality after 12 months of follow‐up (HR adj , 3.91; 95% CI, 2.67 to 5.71; P <0.001).…”
Section: Discussionmentioning
confidence: 99%
“…27) Therefore, additional clopidogrel seems to increase the risk of bleeding and should therefore be used with caution, since major and life-threatening bleeding complications after TAVI are associated with increased mortality. 4) Our study addressed this issue using PRU and CYP2C19 genotyping. The risk of ischemic and bleeding complications was evaluated in each patient using the VerifyNow system, a commercially available system that uses simple blood sampling.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) However, special attention should be paid to potential periprocedural and early complications, including ischemic (stroke, myocardial infarction) or bleeding (access site complication) events. 3,4) After TAVI, guidelines recommend the use of clopidogrel in addition to aspirin for a 3-to 6-month period. [5][6][7] While this strategy has been accepted as the usual practice following TAVI, the recommendation remains empirical and prospective controlled trials are lacking.…”
Section: T Ranscatheter Aortic Valve Implantation (Tavi) Hasmentioning
confidence: 99%
“…Bleeding and ischemic events following TAVI are common, have significant deleterious clinical impact, and may be modifiable with the optimization of post-procedural pharmacology [39,40]. In the absence of an indication for therapeutic anticoagulation, DAPT with aspirin (indefinitely) and clopidogrel has been empirically recommended by consensus of TAVI experts [16,41].…”
mentioning
confidence: 99%